2015
DOI: 10.1002/mma.3398
|View full text |Cite
|
Sign up to set email alerts
|

Hodge decomposition for two‐dimensional time‐harmonic Maxwell's equations: impedance boundary condition

Abstract: We extend the Hodge decomposition approach for the cavity problem of two‐dimensional time‐harmonic Maxwell's equations to include the impedance boundary condition, with anisotropic electric permittivity and sign‐changing magnetic permeability. We derive error estimates for a P1 finite element method based on the Hodge decomposition approach and present results of numerical experiments that involve metamaterials and electromagnetic cloaking. The well‐posedness of the cavity problem when both electric permittivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Let B denote the operator associated with the sesquilinear form b(•, •) defined by (15) where I : H 1 (D R ) → H 1 (D R ) is an isomorphism and where K :…”
Section: Proof Of Decomposition (17)mentioning
confidence: 99%
See 1 more Smart Citation
“…Let B denote the operator associated with the sesquilinear form b(•, •) defined by (15) where I : H 1 (D R ) → H 1 (D R ) is an isomorphism and where K :…”
Section: Proof Of Decomposition (17)mentioning
confidence: 99%
“…Under some assumptions on the meshes, the discretized problem is well-posed and its solution converges to the solution of the continuous problem. Let us mention that the study of Maxwell's equations has been carried out in [10,11,15].…”
Section: Introductionmentioning
confidence: 99%
“…where ǫ 0 and µ 0 are the permittivity and permeability of vacuum, and ǫ and µ are the relative permittivity and permeability of the specific media. There exist many excellent works on the analysis and applications of finite element method (FEM) for solving the Maxwell's equations in various media, such as in the free space (e.g., papers [3,4,6,7,11,16,17,43], books [12,22,30] and references therein); in general dispersive media (e.g., [2,19,28,34]); in negative index metamaterials [18,38,39]; and in cloaking metamaterials [23][24][25]41]. In recent years, we developed some mathematical models and time-domain FEMs for simulating the invisibility cloaks [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…, where is the electric permeability, µ is the magnetic permeability, plus boundary conditions. The study of Maxwell's equation with sign-changing coefficients has been carried out in [3]- [4]- [7]. In particular, in [4], by resorting to the T -coercivity approach, it was shown that electric and magnetic Maxwell transmission problems are well-posed as soon as the associated three-dimensional scalar problems are well-posed.…”
Section: Model Problemmentioning
confidence: 99%